A lithium iron titanate positive electrode material and preparation method thereof
A solid phase reaction method using iron salt and titanium dioxide with controlled calcination produces lithium iron titanate with uniform particle sizes and improved performance, addressing industrial scalability issues in lithium ion batteries.
Patent Information
- Application Number
- CN202211116087.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-09-14
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2042-09-14
AI Technical Summary
Existing methods for producing lithium iron titanate positive electrode materials face challenges such as high synthesis temperatures, long calcination times, high energy consumption, and irregular particle sizes, making them unsuitable for large-scale industrial applications.
A solid phase reaction method using an iron salt with crystal water to react with titanium dioxide, followed by calcination with a lithium source, reduces reaction temperatures and energy consumption while producing a lithium iron titanate material with regular morphology and small particle sizes, suitable for industrial production.
The method achieves low-cost, high-rate performance and charge-discharge efficiency with uniform particle sizes, suitable for industrial-scale lithium ion batteries.
Smart Images

Figure BDA0003845604150000081 
Figure HDA0003845604160000011 
Figure HDA0003845604160000012
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a lithium iron titanate positive electrode material and a preparation method thereof. Background Art
[0002] Lithium-ion batteries have been widely studied due to their advantages such as high energy density, long cycle life, no memory effect and high safety performance. At present, lithium-ion batteries are not only used in mobile electronic products, but also widely used in electric vehicles and hybrid vehicles. Although lithium cobalt oxide batteries have excellent electrochemical performance, cobalt is expensive and toxic, and people are actively looking for substitutes. The development of a positive electrode material with cheap and easy-to-obtain raw materials, safe and environmentally friendly is a current research hotspot. Lithium iron titanate (Li2FeTiO4) with a spinel structure is a new type of positive electrode material with the advantages of abundant raw material sources, safety and environmental protection. During the charge and discharge process, the crystal structure of Li2FeTiO4 positive electrode material basically does not change. It is a zero-strain positive electrode material with a theoretical capacity of 147mAh / g.
[0003] The high-temperature solid-phase method is the most mature process for large-scale production. The traditional high-temperature solid-phase method for preparing Li2FeTiO4 has the disadvantages of high synthesis temperature (such as over 1000°C), long calcination time, high energy consumption, and the obtained product particle size is difficult to control, uneven distribution, irregular morphology, etc. These disadvantages greatly limit the advantages of Li2FeTiO4. In addition, the preparation of Li2FeTiO4 is also carried out in water phase, such as hydrothermal method, sol-gel method, solvothermal method and coprecipitation method. However, these methods are complex, energy-intensive, high in production cost and low in output, and are not suitable for large-scale industrial application. Summary of the invention
[0004] The purpose of the present invention is to provide a method for preparing lithium iron titanate positive electrode material in a solid phase reaction system. Compared with the traditional high-temperature solid phase method, the method of the present invention can greatly reduce the reaction temperature, low energy consumption, low cost, and the obtained lithium iron titanate positive electrode material has a regular morphology, a small average particle size, and excellent charge and discharge efficiency and rate performance, and is suitable for industrial production.
[0005] To achieve this object, the present invention adopts the following technical solutions:
[0006] In a first aspect, the present invention provides a method for preparing a lithium iron titanate positive electrode material, comprising the following steps:
[0007] S1. contacting the iron source with titanium dioxide to produce a solid phase reaction to obtain the lithium iron titanate cathode material precursor;
[0008] S2. Mixing the lithium source with the precursor obtained in step S1 and calcining the mixture to obtain the lithium iron titanate positive electrode material.
[0009] According to some embodiments of the present invention, the iron source is an iron salt with crystal water.
[0010] The present invention uses iron salt with crystal water to react with titanium dioxide in a solid phase system, uses trace crystal water to provide a reaction field, and the two reactant molecules of iron salt and titanium dioxide diffuse and contact, that is, interact with each other, and undergo four stages of diffusion-reaction-nucleation-growth to obtain a lithium iron titanate positive electrode material precursor. Preferably, the rate of nucleation of reactant particles colliding with each other can also be accelerated by extrusion to increase the reaction speed.
[0011] The trace amount of crystal water of the present invention provides a reaction field while not completely solvating the reactants, thereby avoiding the adverse effects of complicated post-processing steps and side reactions on the products caused by a large amount of solvent.
[0012] According to some embodiments of the present invention, the iron source is selected from one or more of FeCl2·4H2O, Fe(NO3)2·9H2O, and FeSO4·7H2O.
[0013] According to some embodiments of the present invention, the molar ratio of iron provided by the iron source to titanium dioxide is 1:(0.5-1.5), for example, 1:0.5, 1:0.6, 1:0.7, 1:0.8, 1:0.9, 1:1, 1:1.1, 1:1.2, 1:1.3, 1:1.4 or 1:1.5, preferably 1:(0.8-1.2).
[0014] According to some embodiments of the present invention, the lithium source is selected from one or more of lithium hydroxide, lithium oxide, lithium carbonate, and lithium acetate. The preferred lithium source in the present invention is lithium hydroxide monohydrate.
[0015] According to some embodiments of the present invention, the molar ratio of the lithium element provided by the lithium source to the iron element in the precursor is 2:(0.5-1.5), for example, 2:0.5, 2:0.6, 2:0.7, 2:0.8, 2:0.9, 2:1, 2:1.1, 2:1.2, 2:1.3, 2:1.4 or 2:1.5, preferably 2:(0.8-1.2).
[0016] According to some embodiments of the present invention, the contacting includes the step of premixing the iron source with titanium dioxide. In some embodiments, the premixing temperature is 0°C to 90°C, for example, 10°C, 20°C, 25°C, 30°C, 35°C, 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 80°C; preferably 0°C to 60°C. In some embodiments, the premixing time is 40min to 150min, preferably 50min to 120min. In some embodiments, the premixing speed is 350rpm to 700rpm, for example 400rpm, 420rpm, 450rpm, 480rpm, 500rpm, 520rpm, 550rpm, 580rpm, 600rpm, 650rpm or 700rpm, preferably 400rpm to 600rpm.
[0017] According to some embodiments of the present invention, the temperature of the solid phase reaction is 420-650°C, for example 420°C, 440°C, 450°C, 460°C, 480°C, 500°C, 520°C, 540°C, 550°C, 560°C, 580°C, 600°C, 620°C or 650°C, preferably 450-550°C.
[0018] According to some embodiments of the present invention, the solid phase reaction time is 4 h to 10 h, preferably 6 h to 8 h.
[0019] According to some embodiments of the present invention, stirring is performed during the solid phase reaction, and the stirring speed is 30 to 160 rpm, for example, 30 rpm, 40 rpm, 50 rpm, 60 rpm, 70 rpm, 80 rpm, 90 rpm, 100 rpm, 110 rpm, 120 rpm, 130 rpm, 140 rpm, 150 rpm or 160 rpm, preferably 40 to 120 rpm.
[0020] In the present invention, the calcination temperature will affect the size of the obtained lithium iron titanate positive electrode material. A higher calcination temperature will result in a larger particle size of the lithium iron titanate positive electrode material, which is not conducive to improving its rate performance and charge-discharge performance. Therefore, the calcination temperature needs to be controlled within a suitable range.
[0021] According to some embodiments of the present invention, the calcination temperature is 700°C to 900°C, such as 720°C, 750°C, 780°C, 800°C, 820°C, 850°C, 880°C or 900°C, preferably 750°C to 850°C.
[0022] According to some embodiments of the present invention, the calcination time is 8 h to 36 h, preferably 12 h to 24 h.
[0023] Preferably, in step S2, the calcination is performed in a protective gas.
[0024] Further preferably, the protective gas is selected from a mixture of argon and hydrogen.
[0025] According to some embodiments of the present invention, the preparation method comprises the following steps:
[0026] (1) mixing an iron salt with crystal water and titanium dioxide at a temperature of 0° C. to 90° C. to obtain a premix;
[0027] (2) subjecting the premix obtained in step (1) to a solid phase reaction at 450° C. to 550° C. to obtain a lithium iron titanate positive electrode material precursor;
[0028] (3) Mixing the lithium source with the lithium iron titanate positive electrode material precursor obtained in step (2) and calcining the mixture at a temperature of 700° C. to 900° C. to obtain the lithium iron titanate positive electrode material.
[0029] In some embodiments, the molar ratio of the iron element provided by the iron salt in step (1) to titanium dioxide is 1: (0.5-1.5), preferably 1: (0.8-1.2). In some embodiments, the temperature of 0°C to 90°C in step (1) can be 0°C, 10°C, 20°C, 30°C, 40°C, 50°C, 60°C, 70°C, 80°C, 90°C and any value therebetween. In some embodiments, the reaction time in step (2) is 4h to 10h, preferably 6h to 8h. In some embodiments, the molar ratio of the lithium source in step (3) to the iron element in the precursor is 2: (0.5-1.5), preferably 2: (0.8-1.2). In some embodiments, the calcination time in step (3) is 8h to 36h, preferably 12h to 24h.
[0030] Preferably, the calcination in step (3) is carried out in a protective gas.
[0031] Further preferably, the protective gas is selected from a mixture of argon and hydrogen.
[0032] According to some embodiments of the present invention, the lithium iron titanate positive electrode material precursor includes FeTiO3.
[0033] In a second aspect, the present invention provides a lithium iron titanate positive electrode material obtained by the preparation method described in the first aspect.
[0034] According to some embodiments of the present invention, the average particle size of the lithium iron titanate is 50 nm to 500 nm.
[0035] In a third aspect, the present invention provides the use of the lithium iron titanate positive electrode material obtained by the preparation method described in the first aspect or the lithium iron titanate positive electrode material described in the second aspect in a lithium ion battery.
[0036] Compared with the prior art, the present invention has the following advantages:
[0037] (1) The present invention first utilizes an iron salt with crystal water to react with titanium dioxide in a solid phase to obtain a precursor, and then calcines the precursor with a lithium source at a high temperature to obtain a lithium iron titanate material. No organic or inorganic solvent is required in the reaction, thereby avoiding the complicated post-processing steps and adverse effects of side reactions on the product caused by a large amount of solvent.
[0038] (2) The lithium iron titanate material obtained by the preparation method provided by the present invention has a small and uniform particle size and has high rate performance and charge and discharge performance;
[0039] (3) Compared with the traditional high-temperature solid-phase method, the method of the present invention has low reaction temperature, low energy consumption, and low cost, and is suitable for industrial large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 This is the XRD pattern of the precursor prepared in Example 1.
[0041] Figure 2 This is a scanning electron microscope image of the precursor prepared in Example 1.
[0042] Figure 3 This is the XRD pattern of lithium iron titanate prepared in Example 1.
[0043] Figure 4 This is a scanning electron microscope image of the lithium iron titanate prepared in Example 1. DETAILED DESCRIPTION
[0044] In order to make the purpose, technical scheme and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments and drawings. These embodiments and drawings are only used to explain the present invention and are not intended to constitute any limitation of the present invention. The actual protection scope of the present invention is set forth in the claims.
[0045] Example 1
[0046] This embodiment provides a method for preparing a lithium iron titanate material, comprising the following steps:
[0047] 1.71kg Fe(NO3)2·9H2O and 0.40kg TiO2 were weighed and added to a mixer according to a 1:1 molar ratio. The high-speed cold mixing time was 50min, the stirring speed was controlled at 400rpm, and the temperature was controlled at 30°C. The mixed material was transported to a parallel twin-screw extruder through a transport pipeline for extrusion mixing reaction. The main engine speed was 40 rpm, the current was 50% of the rated current of the main engine, the extrusion mixing temperature was controlled at 450°C, and the reaction time was 6h. The extruded paste was added to deionized water and stirred and mixed, and then centrifuged and washed to remove soluble inorganic salts. After being dried by hot air circulation at 90°C, it was scattered and sieved to obtain FeTiO3 (its XRD results are shown in Figure 1 The results of scanning electron microscopy are shown in Figure 2 ), then mixed with LiOH·H2O in a molar ratio of 1:2, and calcined at 800℃ for 12h in an argon-hydrogen mixed gas (Ar95%+H25%) atmosphere to obtain Li2FeTiO4. The XRD results are shown in Figure 3 , SEM results are shown in Figure 4 .
[0048] Example 2
[0049] This embodiment provides a method for preparing a lithium iron titanate material, comprising the following steps:
[0050] 1.71kg Fe(NO3)2·9H2O and 0.40kg TiO2 are weighed and added into a mixer according to a molar ratio of 1:1, the high-speed cold mixing time is 80min, the stirring speed is controlled at 450rpm, and the temperature is controlled at 40°C; the mixed material is transported to a parallel twin-screw extruder through a transport pipeline for extrusion mixing reaction, the main engine speed is 60 rpm, the current is 60% of the rated current of the main engine, the extrusion mixing temperature is controlled at 450°C, and the reaction time is 6h; the extruded paste is added into deionized water and stirred and mixed, and then centrifuged and washed to remove soluble inorganic salts, and then dried by hot air circulation at 90°C, and then scattered and sieved to obtain a precursor FeTiO3, which is then mixed with LiOH·H2O in a molar ratio of 1:2, and calcined at 800°C for 16h in an argon-hydrogen mixed gas (Ar95%+H25%) atmosphere to obtain Li2FeTiO4.
[0051] Example 3
[0052] This embodiment provides a method for preparing a lithium iron titanate material, comprising the following steps:
[0053] 1.71kg Fe(NO3)2·9H2O and 0.40kg TiO2 are weighed and added into a mixer according to a molar ratio of 1:1, the high-speed cold mixing time is 80min, the stirring speed is controlled at 600rpm, and the temperature is controlled at 50°C; the mixed material is transported to a parallel twin-screw extruder through a transportation pipeline for extrusion mixing reaction, the main engine speed is 80 rpm, the current is 40% of the rated current of the main engine, the extrusion mixing temperature is controlled at 500°C, and the reaction time is 8h; the extruded paste is added into deionized water and stirred and mixed, and then centrifuged and washed to remove soluble inorganic salts, and then dried by hot air circulation at 90°C, and then scattered and sieved to obtain a precursor FeTiO3, which is then mixed with LiOH·H2O in a molar ratio of 1:2, and calcined at 800°C for 20h in an argon-hydrogen mixed gas (Ar95%+H25%) atmosphere to obtain Li2FeTiO4.
[0054] Example 4
[0055] This embodiment provides a method for preparing a lithium iron titanate material, comprising the following steps:
[0056] 1.71kg Fe(NO3)2·9H2O and 0.40kg TiO2 are weighed and added into a mixer according to a molar ratio of 1:1, the high-speed cold mixing time is 120min, the stirring speed is controlled at 450rpm, and the temperature is controlled at 60°C; the mixed material is transported to a parallel twin-screw extruder through a transportation pipeline for extrusion mixing reaction, the main engine speed is 80 rpm, the current is 70% of the rated current of the main engine, the extrusion mixing temperature is controlled at 500°C, and the reaction time is 10h; the extruded paste is added into deionized water and stirred and mixed, and then centrifuged and washed to remove soluble inorganic salts, and then dried by hot air circulation at 90°C, and then scattered and sieved to obtain a precursor FeTiO3, which is then mixed with LiOH·H2O in a molar ratio of 1:2, and calcined at 800°C for 24h in an argon-hydrogen mixed gas (Ar95%+H25%) atmosphere to obtain Li2FeTiO4.
[0057] Example 5
[0058] This embodiment provides a method for preparing a lithium iron titanate material, comprising the following steps:
[0059] 1.71kg Fe(NO3)2·9H2O and 0.40kg TiO2 were weighed and added into a mixer according to a molar ratio of 1:1, the high-speed cold mixing time was 50min, the stirring speed was controlled at 500rpm, and the temperature was controlled at 30°C; the mixed material was transported to a parallel twin-screw extruder through a transport pipeline for extrusion mixing reaction, the main engine speed was 120 rpm, the current was 70% of the rated current of the main engine, the extrusion mixing temperature was controlled at 550°C, and the reaction time was 10h; the extruded paste was added into deionized water and stirred and mixed, and then centrifuged and washed to remove soluble inorganic salts, and then dried by hot air circulation at 90°C, and then scattered and sieved to obtain a precursor FeTiO3, which was then mixed with LiOH·H2O in a molar ratio of 1:2, and calcined at 800°C for 28h in an argon-hydrogen mixed gas (Ar95%+H25%) atmosphere to obtain Li2FeTiO4.
[0060] Example 6
[0061] This embodiment provides a method for preparing lithium iron titanate material, which is different from Embodiment 1 only in that "the extrusion mixing temperature is controlled at 450° C." is replaced by "the extrusion mixing temperature is controlled at 550° C.".
[0062] Example 7
[0063] This embodiment provides a method for preparing lithium iron titanate material, which is different from Embodiment 1 only in that "extrusion mixing reaction time 6 hours" is replaced by "extrusion mixing reaction time 8 hours".
[0064] Example 8
[0065] This embodiment provides a method for preparing a lithium iron titanate material, which is different from Embodiment 1 only in that "extrusion mixing reaction time 6 hours" is replaced by "extrusion mixing reaction time 10 hours".
[0066] Example 9
[0067] This embodiment provides a method for preparing lithium iron titanate material, which is different from Embodiment 1 only in that "main engine speed of 40 rpm" is replaced by "main engine speed of 80 rpm".
[0068] Example 10
[0069] This embodiment provides a method for preparing lithium iron titanate material, which is different from Embodiment 1 only in that "main engine speed of 40 rpm" is replaced by "main engine speed of 120 rpm".
[0070] Embodiment 11
[0071] This embodiment provides a method for preparing lithium iron titanate material, which is different from Embodiment 1 only in that "main engine speed of 40 rpm" is replaced by "main engine speed of 160 rpm".
[0072] Example 12
[0073] This embodiment provides a method for preparing a lithium iron titanate material, which is different from Embodiment 1 only in that "the temperature is controlled at 30° C." is replaced by "the temperature is controlled at 0° C.".
[0074] Embodiment 13
[0075] This embodiment provides a method for preparing a lithium iron titanate material, which is different from Embodiment 1 only in that "the temperature is controlled at 30° C." is replaced by "the temperature is controlled at 60° C.".
[0076] Embodiment 14
[0077] This embodiment provides a method for preparing a lithium iron titanate material, which is different from Embodiment 1 only in that “the temperature is controlled at 30° C.” is replaced by “the temperature is controlled at 90° C.”
[0078] Embodiment 15
[0079] This embodiment provides a method for preparing a lithium iron titanate material, which is different from Embodiment 1 only in that “calcining at 800° C. for 12 h” is replaced by “calcining at 900° C. for 12 h”.
[0080] Comparative Example 1
[0081] This comparative example provides a method for preparing a lithium iron titanate material, comprising the following steps:
[0082] 1.71kg Fe(NO3)2·9H2O and 0.40kg TiO2 were weighed and added into a mixer in a molar ratio of 1:1. The high-speed cold mixing time was 50min, the stirring speed was controlled at 500rpm, and the temperature was controlled at 30°C. The mixed material was transported to a parallel twin-screw extruder through a transport pipeline for extrusion mixing reaction. The main engine speed was 80 rpm, the current was 70% of the rated current of the main engine, the extrusion mixing temperature was controlled at 400°C, and the reaction time was 10h. The extruded product was still a white mixed powder, and a FeTiO3 precursor could not be obtained.
[0083] Comparative Example 2
[0084] This comparative example provides a preparation method of lithium iron titanate material, which is different from Example 1 only in that "the extrusion mixing temperature is controlled at 450°C" is replaced by "the extrusion mixing temperature is controlled at 400°C", and FeTiO3 cannot be obtained.
[0085] Comparative Example 3
[0086] This comparative example provides a preparation method of lithium iron titanate material, which is different from Example 1 only in that "the extrusion mixing temperature is controlled at 450° C." is replaced by "the extrusion mixing temperature is controlled at 800° C.".
[0087] Effect test
[0088] The lithium iron titanate materials obtained in Example 1-14 and Comparative Example 1-3 are prepared into a lithium ion battery using the same method. The preparation method is as follows:
[0089] The prepared Li2FeTiO4 powder is mixed with the conductive agent acetylene black and the binder PVDF (polyvinylidene fluoride) in a mass ratio of 8:1:1. The conductive agent and Li2FeTiO4 powder are fully ground in an agate mortar, and then added to the mixture of the binder and NMP (N-methylpyrrolidone) that has been fully stirred, and stirred into a uniform slurry. Use a scraper to coat it on aluminum foil, and then place it in a pinhole drying oven at a constant temperature of 100°C for 12 hours to completely evaporate the solvent. Then, the dried electrode is punched into an electrode sheet with a diameter of 12 mm using a mold. The prepared electrode sheet was used as the positive electrode, the lithium sheet as the negative electrode, the polypropylene porous membrane as the separator, and 1 mol / L LIPF6EC:DMC:EMC (volume ratio 1:1:1) as the electrolyte. A button cell (CR2032) was assembled in an argon-protected glove box. A blue electric tester was used for constant current charge and discharge tests. The charge and discharge voltage range was 1.5-4.8 V. The test results are shown in Table 1.
[0090] Table 1
[0091]
[0092] It can be seen from the results of Comparative Examples 1 and 2 that when the extrusion mixing temperature is 400°C, the precursor FeTiO3 cannot be prepared; while from the results of Example 1, Example 6 and Comparative Example 3, it can be seen that when the extrusion mixing temperature is in the range of 450-550°C, the discharge capacity of the obtained positive electrode material is higher.
[0093] By comparing the results of Example 1 and Examples 7-8, it can be seen that within 6h-8h, the longer the extrusion mixing time is, the more complete the mixing is, and the higher the discharge capacity of the positive electrode material is.
[0094] By comparing the results of Example 1 and Examples 9-11, it can be seen that within the range of 40 rpm to 120 rpm, the higher the host speed, the more complete the reaction and the higher the discharge capacity of the positive electrode material.
[0095] By comparing the results of Example 1 and Examples 12-14, it can be seen that within the range of 0°C-60°C, the higher the mixing temperature, the more complete the reaction, and the higher the discharge capacity of the positive electrode material.
[0096] By comparing the results of Example 1 and Example 15, it can be seen that the discharge capacity of the positive electrode material obtained by calcining at a temperature of 800°C is higher than that of the positive electrode material calcined at 900°C.
[0097] The technical solution of the present invention is not limited to the above-mentioned specific embodiments. All technical variations made according to the technical solution of the present invention fall within the protection scope of the present invention.
Claims
1. A method for preparing a lithium iron titanate positive electrode material, comprising the following steps: S1. contacting an iron source with titanium dioxide to produce a solid phase reaction to obtain a lithium iron titanate cathode material precursor; S2. The lithium source is mixed with the precursor obtained in step S1 and calcined to obtain the lithium iron titanate cathode material; The temperature of the solid phase reaction is 450°C to 550°C; the time of the solid phase reaction is 6h to 8h; The iron source is one or more of FeCl2·4H2O, Fe(NO3)2·9H2O, and FeSO4·7H2O; the contacting comprises the step of premixing the iron source with titanium dioxide; The premixing temperature is 0°C to 60°C; the premixing time is 50min to 120min; The solid phase reaction is carried out in a parallel twin-screw extruder; Stirring is performed during the solid phase reaction, and the stirring speed is 40 to 120 rpm; The calcination temperature is 700°C to 900°C; the calcination time is 8h to 36h; The lithium iron titanate positive electrode material includes Li2FeTiO4; The lithium iron titanate positive electrode material precursor includes FeTiO3.
2. The preparation method according to claim 1, characterized in that: The molar ratio of the iron element provided by the iron source to titanium dioxide is 1:(0.5-1.5).
3. The preparation method according to claim 1, characterized in that: The molar ratio of the iron element provided by the iron source to titanium dioxide is 1:(0.8-1.2).
4. The preparation method according to claim 1, characterized in that: The lithium source is selected from one or more of lithium hydroxide, lithium oxide, lithium carbonate and lithium acetate; And / or the molar ratio of the lithium element provided by the lithium source to the iron element in the precursor is 2: (0.5~1.5).
5. The preparation method according to claim 1, characterized in that: The molar ratio of the lithium element provided by the lithium source to the iron element in the precursor is 2: (0.8-1.2).
6. The preparation method according to claim 1, characterized in that: The calcination temperature is 750° C. to 850° C.; the calcination time is 12 h to 24 h.
7. The preparation method according to claim 1, characterized in that: The average particle size of the lithium iron titanate is 50nm~500nm.
8. Use of the lithium iron titanate positive electrode material obtained by the preparation method according to any one of claims 1 to 7 in lithium ion batteries.
